BETWEEN ROOTS AND NEW HORIZONS: : CULTURAL IDENTITY OF RURAL YOUTH FROM AN EDUCATIONAL PERSPECTIVE (Interdisciplinary Studies Journal, 2026)
Cultural identity development is a result of experiences one lives in multiple spaces. This is a dynamic concept and it is constantly transforming. On this basis, this article aims to analyze different types of cultural identity manifestation among students from a rural school. The methodological approach consists of quali-quantitative research, including semi-structured questionnaires that were applied to students of the rural area in order to understand some aspects, such as daily habits, family relations, technology and social media, as well as expectations for the future after graduating high school. The data analysis revealed that these young people live between traditional values and modern times, showing that they belong to several spaces and reframing the concept of “being” in the countryside. The identities considered for this research show hybrid characteristics, meaning they are constantly between rural and urban spaces, which confirms the importance of an educational perspective in order to promote appreciation and cultural mediation in these people considering the different spaces. This study aims to ponder on the role of the education in the integral formation of young people and the affirmation of their socio-territorial bond.
Keywords: Youth; Sense of Belonging; Sociocultural Practices